2022
DOI: 10.1111/jog.15402
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal natural orifice transluminal endoscopic surgery in gynecological procedure: Experience of a Women's and Children's Medical Center from China

Abstract: Objective: To review of our hospital's experiences in transvaginal natural orifice transluminal endoscopic surgery (vNOTES) and challenges we encountered in performance of the procedure, so as to provide help to medical institutions who are preparing to carry out vNOTES. Methods: We retrospectively analyzed the data of all patients receiving vNOTES in our hospital from April 2018 to May 2021. Data we collected cover the general characteristics, perioperative outcomes, and complications of the patients. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has been conducted in our institute for only 4 years. 17 We have performed 3000 cases of vNOTES so far, but because not many patients would suffer from another benign gynecological disease in such a short period after the first vNOTES, we did not have many patients who underwent a second vNOTES. Thus, we only had a few cases of repeated vNOTES, making the study on the repeatability of vNOTES challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been conducted in our institute for only 4 years. 17 We have performed 3000 cases of vNOTES so far, but because not many patients would suffer from another benign gynecological disease in such a short period after the first vNOTES, we did not have many patients who underwent a second vNOTES. Thus, we only had a few cases of repeated vNOTES, making the study on the repeatability of vNOTES challenging.…”
Section: Discussionmentioning
confidence: 99%
“…vNOTES is an emerging minimally invasive surgical technique, which has not been widely performed worldwide. It has been conducted in our institute for only 4 years 17 . We have performed 3000 cases of vNOTES so far, but because not many patients would suffer from another benign gynecological disease in such a short period after the first vNOTES, we did not have many patients who underwent a second vNOTES.…”
Section: Discussionmentioning
confidence: 99%
“…The vNOTES and TU-LESS procedures performed and the equipment applied in the present study will be similar to those described in previous publications. [24,33,41,42] Recruitment procedures and follow-up plan Recruitment: The enrolment owchart and follow-up plan for the CLOCKBEGIN study are shown in Fig. 1.…”
Section: Study Interventionsmentioning
confidence: 99%
“…This study applied similar surgical methods and equipment as described in previous publications [6,9,10]. The detailed surgical procedures were as follows:…”
Section: Operating Procedures Of Vnotes Ovarian Cystectomymentioning
confidence: 99%